Comprehensive structural analysis of the open and closed conformations of Theileria annulata enolase by molecular modelling and docking. (October 2016) - Mutlu, Ozal; Yakarsonmez, Sinem; Sariyer, Emrah; Danis, Ozkan; Yuce-Dursun, Basak; Topuzogullari, Murat; Akbulut, Ekrem; Turgut-Balik, Dilek
Graphical abstract: Highlights: We have modeled three-dimensional structure of Theileria annulata enolase with open and closed conformations. Comparative analysis shows conserved active site residues, folding patterns and domains. Surface pockets and electrostatic properties represent promising druggable sites. Docking efforts suggest binding mode of 2-PGA with high accuracy. Abstract: Theileria annulata is an apicomplexan parasite which is responsible for tropical theileriosis in cattle. Due to resistance of T. annulata against commonly used antitheilerial drug, new drug candidates should be identified urgently. Enolase might be a druggable protein candidate which has an important role in glycolysis, and could also be related to several cellular functions as a moonlight protein. In this study; we have described three-dimensional models of open and closed conformations of T. annulata enolase by homology modeling method for the first time with the comprehensive domain, active site and docking analyses. Our results show that the enolase has similar folding patterns within enolase superfamily with conserved catalytic loops and active site residues. We have described specific insertions, possible plasminogen binding sites, electrostatic potential surfaces and positively charged pockets as druggable regions in T. annulata enolase.